2020
DOI: 10.1016/j.seizure.2020.06.032
|View full text |Cite
|
Sign up to set email alerts
|

The role of chronobiology in drug-resistance epilepsy: The potential use of a variability and chronotherapy-based individualized platform for improving the response to anti-seizure drugs

Abstract: Despite progress in the development of anti-seizure drugs, drug-resistant epilepsy (DRE) occurs in a third of patients. DRE is associated with poor quality of life and increased risk of sudden, unexplained death. The autonomic nervous system and chronobiology play a role in DRE. In the present paper, we provide a narrative review the mechanisms that underlie DRE and characterize some of the autonomic-and chronotherapy-associated parameters that contribute to the degree of response to therapy. Variability descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 213 publications
0
40
0
2
Order By: Relevance
“…This enables the overcoming of intra-and inter-patient variability, which prevents the "single bullet for all" concept from being applicable to the majority of patients. This concept is being introduced for overcoming drug resistance in several chronic diseases (142,143,(145)(146)(147)(148)(149)(150)(151)(152)(153)(154)(155)(156). In the last step, signatures based on parameters relevant to the pathogenesis of HF, mechanisms of action, and the cardio renal axis are introduced in a personalized approach for tailoring the appropriate dosing in a continuous and consistent manner (143, 144) (Figure 2).…”
Section: Establishing a Chronotherapy And Variability-based Algorithm For Improving The Response To Effectivenss Of Diureticsmentioning
confidence: 99%
“…This enables the overcoming of intra-and inter-patient variability, which prevents the "single bullet for all" concept from being applicable to the majority of patients. This concept is being introduced for overcoming drug resistance in several chronic diseases (142,143,(145)(146)(147)(148)(149)(150)(151)(152)(153)(154)(155)(156). In the last step, signatures based on parameters relevant to the pathogenesis of HF, mechanisms of action, and the cardio renal axis are introduced in a personalized approach for tailoring the appropriate dosing in a continuous and consistent manner (143, 144) (Figure 2).…”
Section: Establishing a Chronotherapy And Variability-based Algorithm For Improving The Response To Effectivenss Of Diureticsmentioning
confidence: 99%
“…Chronotherapies and personalization of treatment schedules to accommodate sleeprelated epilepsy also provides a useful avenue for personalized seizure prevention [126,353,354]. For example, Guilhoto et al [132] observed that a higher dose of antiepileptic drugs (AEDs) at night led to seizure freedom in 64.7% (11/17) of patients, and 88.2% (15/17) experienced reduced seizure frequency.…”
Section: Chronotherapiesmentioning
confidence: 99%
“…B. alle 3-6 Monate) beziehen [52]. Das Wissen um solche Zyklen ermöglicht zum einen Vorsorgemaßnahmen und die Etablierung individueller Therapieanpassungen (Chronopharmakotherapie) [54][55][56]. Zum anderen können Vorhersage-Algorithmen durch Berücksichtigung der zyklischen Muster relevant verbessert werden [57].…”
Section: Anfallsvorhersageunclassified
“…Erst die Validierung solcher Technologien nach höchsten Gütekriterien auch unter nicht kontrollierten Bedingungen (Phase 4-Studie nach [12]) wird den zuverlässigen Einsatz im häuslichen Umfeld und in Einrichtungen, aber auch in randomisierten klinischen Studien zur Wirksamkeitsprüfung von Medikamenten, implantierten Neurostimulation-Systemen und epilepsiechirurgischen Eingriffen erlauben. Eine objektive, automatisierte Zählung über einen längeren Zeitraum könnte auch neue Erkenntnisse zu individuellen zyklischen Mustern epileptischer Anfälle liefern und chronopharmakologische Therapieansätze ermöglichen [52,[54][55][56]. Die unmittelbare Kopplung von Detektions-und Vorhersagetechnologien mit Interventionsmöglichkeiten in einer Closed-Loop könnte auch beginnende Anfälle unterbrechen, wie es bereits bspw.…”
Section: Perspektivenunclassified